IoT based Smart Fault Identification and Monitoring System for Electric Poles - M, Mohammed Mushraf.; C, Krishnapriya; S, Balamurugan (Journal of Electronics and Informatics, 2024)
Electricity is essential in modern life, but damaged power lines cause thousands of electrocutions in India every year. To fix a damaged power line, the power supply is turned off, and a fuse controller is placed on the electric feeder. If the fuse controller trips on a broken wire, the electricity is cut off until the damage is located. This process can be time-consuming and requires resources. This research aims to design a IoT based control system to reduce the time for repairing broken electrical lines and prevent accidents by adopting measures to expedite the repair process, enhance safety, and optimize maintenance efficiency. LoRa devices are installed every 1 km along the cable for a total range of 10 km. A central tower marks the halfway point. A single LoRa device at the tower may be more cost-effective than multiple devices at each pole. A control circuit embedded by transistor and diode safeguard the circuit's integrity and ensure current flows in a single direction, protecting it if a wire between two poles is damaged. After locating damage to a pole, an email is sent to the relevant authority, including location, pole number, and incident time. An automatic alarm will sound when electricity is turned off, warning the public of the danger. Additionally, this system saves time and resources, and is cost-effective.
Keywords: IOT; electrocutions; LoRa; Fault Identification; Electric Poles